2014
DOI: 10.5812/ircmj.20024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Educational Intervention on Health-Promoting Lifestyle and Health-Related Life quality of Methamphetamine Users and Their Families: a Randomized Clinical Trial

Abstract: Background:Family-centered empowerment of drug and stimulant users is an effective program for a better response to treatment, prevention of treatment adverse effects, and promotion quality of life (QoL) and lifestyle in the process of discontinuing drug abuse.Objectives:This study aimed to determine the effects of educational intervention, based on family-centered empowerment and Pender's health promotion models, on health-promoting lifestyle and health-related QoL among methamphetamine users and their famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
(34 reference statements)
0
13
0
2
Order By: Relevance
“…It has been proven by researchers that exercise has a positive impact on health. Ghasemi et al (2014) studied the effect of educational intervention on lifestyle and quality of life in relation to the health of patients with methamphetamine abuse and their families. The results indicated that the application of a family-oriented empowerment model among patients with methamphetamine abuse and their families can increase and improve their quality of life and lifestyle, which consequently promotes their health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proven by researchers that exercise has a positive impact on health. Ghasemi et al (2014) studied the effect of educational intervention on lifestyle and quality of life in relation to the health of patients with methamphetamine abuse and their families. The results indicated that the application of a family-oriented empowerment model among patients with methamphetamine abuse and their families can increase and improve their quality of life and lifestyle, which consequently promotes their health.…”
Section: Discussionmentioning
confidence: 99%
“…Amphetamine abuse most often leads to several outcomes including severe mental, marital, and socioemotional problems; criminal involvements; and job instability, all of which impact quality of life and lifestyles in amphetamine abusers (Epstein, Ryan, Bishop, Miller, & Keitner, 2003). In the study conducted by Ghasemi, Estebsari, Bastaminia, Jamshidi, and Dastoorpoor (2014), effects of educational interventions on healthy lifestyles and quality of life of amphetamine abusers and their families were determined based on family-oriented empowerment and Pender's health promotion model. The results showed that application of the family-oriented empowerment model among methamphetamine abusers and their families effectively increases and improves quality of life and lifestyles, leading to the development of a health promotion model (Ghasemi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The German manual is available free of charge from the corresponding author and has been described in detail elsewhere (12). In summary, it features a methamphetamine-specific relapse prevention program based on motivational interviewing, which comprises 15 modules: [1] introduction to treatment rationale including functional analysis of last methamphetamine consumption, [2+6] motivational clarification and enhancement (if necessary also in further course of therapy), [3−5] understanding and managing of cravings, [7−9] the role of the social environment and role-play training of strategies to resist drug use, [10+11] awareness of seemingly irrelevant decisions, [12+13] identifying and dealing with other high-risk situations, [14] drafting a personal crisis plan, [15] coping with problems after the end of therapy. The 15 sessions lasted 50 min each and were delivered to groups of up to 6 participants by a psychotherapist twice a week.…”
Section: Interventionmentioning
confidence: 99%
“…Utilizou-se para coleta um questionário demográfico criado pelo autor e a Health Promotion Lifestyle Profile (HPLP) que mede as frequências dos comportamentos de promoção da saúde em seis áreas: auto realização, responsabilidade para saúde, atividade física, nutrição, relação interpessoal, e gestão do stress (12) . O ensaio clínico randomizado, realizado com usuários de metanfetamina em recuperação e membros da família, utilizou para sua coleta de dados o Modelo de Promoção da Saúde de Pender (PHPM) e o Modelo de Empoderamento Centrado na Família (FCEM) para avaliar uma intervenção educativa (13) .…”
Section: Metodologias Para Promoção Da Saúde Familial Nos Diferentes unclassified
“…Assim, o familiar que participa do processo fortalece as relações com o individuo que precisa do cuidado (13) . 19:431 , outro estudo, apresentou a definição de Promoção da Saúde da Família, como diferente de prevenção das doenças, ela é um conjunto de fatores com foco no aumento do bem-estar e qualidade de vida da família (15) .…”
Section: Metodologias Para Promoção Da Saúde Familial Nos Diferentes unclassified